Development and evaluation of colon targeted drug delivery system by using natural Polysaccharides/Polymers - Godge, GR; Hiremath, SN (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Colon is being extensively investigated as a drug delivery site. This study contains comparison of the usual enteric coating polymers viz. xanthan gum, guar gum, chitosan and ethyl cellulose, as carriers for colon specific drug delivery. Lactose based metoprolol succinate tablets were prepared. These were coated with one of the coating polymers to a varying coat thickness. Tablets were prepared using polysaccharides or synthetic polymer as binders. These included xanthan gum, guar gum, chitosan and ethyl cellulose. Metoprolol Succinate was used as a model drug. The prepared tablets were enteric coated with kollicoat MAE 100 DP to give protection in the stomach. The coated tablets were tested in-vitro for their suitability as colon specific drug delivery systems. The drug release studies were carried out in simulated stomach environment (pH 1.2) for 2 h followed by small intestinal environment at pH 6.8. The dissolution data obtained from tablets demonstrates that the dissolution rate of the tablet is dependent upon the type and concentration of polysaccharide/polymer used as binder. The results demonstrate that enteric coated tablets containing 3% chitosan as a binder, showed only 12.5% drug release in the first 5 h, which is the usual upper gastrointestinal transit time, whereas, tablets prepared using guar gum as binder, were unable to protect drug release under similar conditions. Preparations with xanthan gum as a binder formed time-dependent release formulations. When used in a concentration of 5.92% in the tablets, 28% drug release was observed in the usual upper gastrointestinal tract conditions. It was also found that enteric coated preparation formulated with 8.88% of kollicoat MAE 100 DP as binder could be used to carry water insoluble drug molecules. The above study shows that chitosan could be successfully used as a binder, for colon targeting of water insoluble drugs in preference to guar gum when used in the same concentration. Additionally, formulations developed with chitosan and kollicoat MAE 100 DP would be highly site specific since drug release would be at a retarded rate till microbial degradation or polymer solubilization takes place in the colon. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21874 Dhaka Univ. J. Pharm. Sci. 13(1): 105-113, 2014 (June)